2016
DOI: 10.1371/journal.pone.0165036
|View full text |Cite
|
Sign up to set email alerts
|

Non-Communicable Disease Risk Factors among Employees and Their Families of a Saudi University: An Epidemiological Study

Abstract: ObjectivesTo assess the prevalence of noncommunicable disease (NCD) risk factors among Saudi university employees and their families; to estimate the cardiovascular risk (CVR) amongst the study population in the following 10years.MethodsThe NCD risk factors prevalence was estimated using a cross-sectional approach for a sample of employees and their families aged ≥ 18 years old, in a Saudi university (Riyadh in Kingdom of Saudi Arabia; KSA). WHO STEPwise standardized tools were used to estimate NCD risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 38 publications
6
51
3
1
Order By: Relevance
“…One study in Barbados found that university staff who older than 45 years old identified have atleast one of chronic diseases risk factors (smoking, lack of physical activity, obesity, lack of vegetables and fruits consumption, and raised blood pressure) and more than half of them have all three risk factors (Morris, Unwin, Ali, Brathwaite-Graham, Samuels, 2011). Almost similar findings identified in one study conducted among staffs of one university in Saudi Arabia (Alzeidan R, Rabiee F, Mandil A, Hersi A, & Fayed A, 2016). In Indonesian context, a study identified that family history and gender as significant hypertensionassociated risk factors among staffs in one public university in West Java (Azra, 2016).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…One study in Barbados found that university staff who older than 45 years old identified have atleast one of chronic diseases risk factors (smoking, lack of physical activity, obesity, lack of vegetables and fruits consumption, and raised blood pressure) and more than half of them have all three risk factors (Morris, Unwin, Ali, Brathwaite-Graham, Samuels, 2011). Almost similar findings identified in one study conducted among staffs of one university in Saudi Arabia (Alzeidan R, Rabiee F, Mandil A, Hersi A, & Fayed A, 2016). In Indonesian context, a study identified that family history and gender as significant hypertensionassociated risk factors among staffs in one public university in West Java (Azra, 2016).…”
Section: Introductionsupporting
confidence: 67%
“…In this study, almost half of respondents (49.25%) projected to have > 10% risk for developing CVD within the next 10 years compare to 25% found in the study conducted in Saudi Arabia (Alzeidan et al, 2016). Age of the respondent paricipated is one of the reasons causing this different.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The current investigation was a substudy of a larger study (n= 4500 subjects) and focused only on non-Saudi employees and their families (n=1437). The details of the larger study and participants' recruitment procedure are described elsewhere (14).…”
Section: Methodsmentioning
confidence: 99%
“…Body weight and height and waist and hip circumferences were measured for all participants, as described previously (14). Questions about lifestyle behaviour, including diet, physical activity and tobacco use, were asked twice: (1) to describe their current behaviour and (2) to report their behavioural habits before moving to Saudi Arabia.…”
Section: Methodsmentioning
confidence: 99%